2004
DOI: 10.1021/bi035636s
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated p40PHOX as a Negative Regulator of NADPH Oxidase

Abstract: The leukocyte NADPH oxidase catalyzes the production of O(2)(-) from oxygen at the expense of NADPH. Activation of the enzyme requires interaction of the cytosolic factors p47(PHOX), p67(PHOX), and Rac2 with the membrane-associated cytochrome b(558). Activation of the oxidase in a semirecombinant cell-free system in the absence of an amphiphilic activator can be achieved by phosphorylation of the cytosolic factor p47(PHOX) by protein kinase C. Another cytosolic factor, p40(PHOX), was recently shown to be phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 38 publications
(81 reference statements)
2
48
1
2
Order By: Relevance
“…The lack of effects on gp91 phox gene expression suggests that cascade overactivation can antagonize functions of NADPH oxidase components via post-translational modifications. Indeed, serine phosphorylation regulates the activities of several components, including p47 phox , p67 phox and Rap1, and threonine phosphorylation of p40 phox inhibits NADPH oxidase function [45][46][47][48]. Despite this antagonistic role, the cascade is required in mature neutrophils but CKLiK expression levels may be insufficient to positively regulate NADPH oxidase components in the absence of CaMKKα activities.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effects on gp91 phox gene expression suggests that cascade overactivation can antagonize functions of NADPH oxidase components via post-translational modifications. Indeed, serine phosphorylation regulates the activities of several components, including p47 phox , p67 phox and Rap1, and threonine phosphorylation of p40 phox inhibits NADPH oxidase function [45][46][47][48]. Despite this antagonistic role, the cascade is required in mature neutrophils but CKLiK expression levels may be insufficient to positively regulate NADPH oxidase components in the absence of CaMKKα activities.…”
Section: Discussionmentioning
confidence: 99%
“…production. However, there are also published reports indicating that p40 phox is an inhibitory molecule for NADPH oxidase activation, in both K562 cells (48) and cell-free assays (49,50). In light of the controversy surrounding the exact role of p40 phox in NADPH oxidase activation, we sought to examine this cytosolic protein, which is absent from the epithelial COS-phox cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that phosphorylation occurs within p40 phox at Thr154 and Ser315 (Bouin et al, 1998) and that phosphorylation of Thr154, but not Ser315, inhibits Nox2 activation (Lopes et al, 2004). Therefore, we made mutants of GFP-p40 phox that could not be phosphorylated [GFPp40 phox (T154A) and GFP-p40 phox (S315A)] or mimic the phosphorylated states [GFP-p40 phox (T154D) and GFP-p40 phox (S315D)].…”
Section: Accumulation Of P40 Phox (Px) At the Phagosome During Fc␥r-mmentioning
confidence: 99%
“…There are, however, no reports of p40 phox defects or deficiencies resulting in CGD. There is some controversy on the precise function of p40 phox , because both Nox2-inhibitory (Sathyamoorthy et al, 1997;Vergnaud et al, 2000;Lopes et al, 2004) and Nox2-supporting effects of p40 phox (Tsunawaki et al, 1996;Cross, 2000;Ellson et al, 2001b;Kuribayashi et al, 2002;He et al, 2004) have been reported. However, recent studies in p40 phox -deficient mice or in Fc␥IIA receptor-reconstituted cells indicate p40 phox is an essential component of the Nox2 system (Ellson et al, 2006;Suh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation